2014
DOI: 10.1038/bjc.2014.482
|View full text |Cite
|
Sign up to set email alerts
|

A survey study of women’s responses to information about overdiagnosis in breast cancer screening in Britain

Abstract: Background:There is concern about public understanding of overdiagnosis in breast cancer screening, and uncertainty about the likely impact on screening participation.Methods:In a population-based survey of 2272 women, we assessed understanding of overdiagnosis and screening intentions before and after exposure to an explanation of overdiagnosis, and one of the three information formats providing an estimate of the rate of overdiagnosis based on the findings of the UK Independent Review.Results:Subjective and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 10 publications
3
47
0
Order By: Relevance
“…A recent survey 41 gave women a very brief explanation of the concept and frequency of overdetection, reporting a small immediate reduction in future screening intentions among those aged 25-46 years. However, participants had little time to process the information, and comprehension appeared suboptimal, leading the authors to suggest that such brief materials may be insufficient to achieve full appreciation of the issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey 41 gave women a very brief explanation of the concept and frequency of overdetection, reporting a small immediate reduction in future screening intentions among those aged 25-46 years. However, participants had little time to process the information, and comprehension appeared suboptimal, leading the authors to suggest that such brief materials may be insufficient to achieve full appreciation of the issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, participants had little time to process the information, and comprehension appeared suboptimal, leading the authors to suggest that such brief materials may be insufficient to achieve full appreciation of the issue. 41 Screening intentions also decreased in a small pilot study of a mammography decision aid (including conceptual information on overdetection) for women over 75 years, but the tool has not been evaluated in a randomised trial. 42 In prostate cancer screening -where the harm of overdetection is well established -decision aids reduced the number of men choosing to screen in meta-analysis of 9 trials.…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60][61][62][63][64][65][66] Specifically, that 100% of our respondents showed a statistically significant preference to avoid harms (FPs, overdiagnosis) is important, because misunderstanding of risk-based harms is common, 67 and recent work exploring attitudes toward overdiagnosis in the context of breast cancer screening has shown considerable confusion as well as limited valuation. [68][69][70][71] Furthermore, the identification of both positive and negative preferences for early diagnosis reinforces qualitative research that suggests the complexity of beliefs about early knowledge of disease in an infant, including concern about the risk of unwanted knowledge and negative consequences for the parent-child bond. 1,9,54 The identification of a negative preference is an important corrective to the literature that identifies early knowledge as valuable in itself, by permitting family adjustment and planning, and averting difficult "diagnostic odysseys."…”
Section: Figurementioning
confidence: 68%
“…For Zikmund-Fisher et al, the most adequate presentation is to use a large denominator (1,000 or 10,000) so that the data can be presented in whole numbers (Zikmund-Fisher et al, 2008). Nevertheless, Waller et al (Waller, Whitaker, Winstanley, Power, & Wardle, 2014) found small differences in the intention to participate between different versions of numerical information. Information expressed in the proportion 1:3 (one life saved for three overdiagnosed women) was associated with a greater decrease in intention to participate than other information formats, although it did not enable a greater understanding of the term "overdiagnosis".…”
Section: Da Review and Further Testingmentioning
confidence: 99%